Electric field-triggered metal-insulator transition resistive switching of bilayered multiphasic VOx - Won, Seokjae; Lee, Sang Yeon; Hwang, Jungyeon; Park, Jucheol; Seo, Hyungtak (Electronic Materials Letters, 2018)
Electric field-triggered Mott transition of VO2 for next-generation memory devices with sharp and fast resistance-switching response is considered to be ideal but the formation of single-phase VO2 by common deposition techniques is very challenging. Here, VOx films with a VO2-dominant phase for a Mott transition-based metal-insulator transition (MIT) switching device were successfully fabricated by the combined process of RF magnetron sputtering of V metal and subsequent O2 annealing to form. By performing various material characterizations, including scanning transmission electron microscopy-electron energy loss spectroscopy, the film is determined to have a bilayer structure consisting of a VO2-rich bottom layer acting as the Mott transition switching layer and a V2O5/V2O3 mixed top layer acting as a control layer that suppresses any stray leakage current and improves cyclic performance. This bilayer structure enables excellent electric field-triggered Mott transition-based resistive switching of Pt-VOx-Pt metal-insulator-metal devices with a set/reset current ratio reaching ~200, set/reset voltage of less than 2.5 V, and very stable DC cyclic switching upto ~120 cycles with a great set/reset current and voltage distribution less than 5% of standard deviation at room temperature, which are specifications applicable for neuromorphic or memory device applications.
Keywords: Deposition technique; Material characterizations; Mott; Resistance switching; Resistive switching; rf-Magnetron sputtering; Scanning transmission electron microscopy; Voltage distribution; MIT; Mott; resistive switching; VO2